2019
DOI: 10.7821/naer.2019.7.431
|View full text |Cite
|
Sign up to set email alerts
|

Projection of the Flipped Learning Methodology in the Teaching Staff of Cross-Border Contexts

Abstract: Technological impact and immigration have resulted in ICT playing a significant role in educational adaptation to multicultural environments. This study focuses on flipped learning as an innovative teaching method. The overall objectives of this research are, on the one hand, to carry out a review of the scientific literature about flipped learning, and, on the other hand, to know the extent of its scope amongst teaching staff in cross-border regions. To achieve these objectives, a quantitative method has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
5
26
0
3
Order By: Relevance
“…The present study intends to confirm the effectiveness that flipped learning has obtained in the field of educational research as reported in the recent impact literature [7,11,13,49,50,[73][74][75]. This effectiveness has been contrasted with the classical and expository methods of knowledge transmission, where the teacher reproduces the contents unilaterally without encouraging the exchange of knowledge and interaction with students [76].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present study intends to confirm the effectiveness that flipped learning has obtained in the field of educational research as reported in the recent impact literature [7,11,13,49,50,[73][74][75]. This effectiveness has been contrasted with the classical and expository methods of knowledge transmission, where the teacher reproduces the contents unilaterally without encouraging the exchange of knowledge and interaction with students [76].…”
Section: Introductionsupporting
confidence: 67%
“…At the forefront of innovative pedagogical trends is flipped learning [6]. This instructional methodology is characterized by being an alternative in educational practice, where the use of information and communication technology (ICT) [7] stands out, investing in the roles of the learning process and giving leadership to students [8,9]. A relevant aspect is the importance that this innovative approach has assumed in the brief temporal space it has in the field of education [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the implementation of flipped learning requires the involvement, training, and dedication of teachers [57], as well as an optimal level of digital competence to generate digital resources [58] and organize and adapt the virtual spaces where the content is located [59,60]. In addition, this approach requires teachers to sometimes dedicate their own time to generating resources to follow, guide, and adequately tutor the student [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…This innovative teaching and learning methodology was created in 2012 by Jonathan Bergmann and Aaron Sams, who developed audiovisual teaching materials so that students with class attendance problems could access the contents from an electronic device connected to the Internet (Bergmann and Sams 2012). From its inception to date, this innovative didactic approach has accrued great relevance, demonstrated by the effectiveness that it grants formative action (He et al 2016;López Belmonte et al 2019;Zainuddin et al 2019).…”
Section: Introductionmentioning
confidence: 99%